(untitled) - International Rice Research Institute (IRRI) (Philippines, 2000)
Frontier project on assessing opportunities for nitrogen fixation in rice (Working group meeting) (3rd : 1999 Aug : Los Baños, Philippines)
Keywords: Agriculture,Nông nghiệp; Organic, chemistry,Hữu cơ, hóa học